Spatial Attention Modulates Initial Afferent Activity in Human Primary Visual Cortex - Kelly, Simon P. (Oxford University Press, 2008)
It is well established that spatially directed attention enhances visual perceptual processing. However, the earliest level at which processing can be affected remains unknown. To date, there has been no report of modulation of the earliest visual event-related potential component “C1” in humans, which indexes initial afference in primary visual cortex (V1). Thus it has been suggested that initial V1 activity is impenetrable, and that the earliest modulations occur in extrastriate cortex. However, the C1 is highly variable across individuals, to the extent that uniform measurement across a group may poorly reflect the dynamics of V1 activity. In the present study we employed an individualized mapping procedure to control for such variability. Parameters for optimal C1 measurement were determined in an independent, preliminary “probe” session and later applied in a follow-up session involving a spatial cueing task. In the spatial task, subjects were cued on each trial to direct attention toward 1 of 2 locations in anticipation of an imperative Gabor stimulus and were required to detect a region of lower luminance appearing within the Gabor pattern 30% of the time at the cued location only. Our data show robust spatial attentional enhancement of the C1, beginning as early as its point of onset (57 ms). Source analysis of the attentional modulations points to generation in striate cortex. This finding demonstrates that at the very moment that visual information first arrives in cortex, it is already being shaped by the brain's attentional biases.